2015
DOI: 10.1164/rccm.201505-0943oc
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Short-Chain Fatty Acids, Produced by Anaerobic Bacteria, in the Cystic Fibrosis Airway

Abstract: Rationale: Anaerobic bacteria are present in large numbers in the airways of people with cystic fibrosis (PWCF). In the gut, anaerobes produce short-chain fatty acids (SCFAs) that modulate immune and inflammatory processes.Objectives: To investigate the capacity of anaerobes to contribute to cystic fibrosis (CF) airway pathogenesis via SCFAs.Methods: Samples of 109 PWCF were processed using anaerobic microbiological culture with bacteria present identified by 16S RNA sequencing. SCFA levels in anaerobic supern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
95
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(112 citation statements)
references
References 43 publications
15
95
0
2
Order By: Relevance
“…We subsequently found that co-culture of pathogens with an anaerobic bacterial consortium composed of taxa commonly found in the lower airways [3,5,27,28] can facilitate robust pathogen growth using mucins as a sole carbon source. We also confirmed that fermentation-derived metabolites are abundant within expectorated CF patient sputum, consistent with previous studies [14,29]. Finally, we found that genes required for the catabolism of mucin fermentation byproducts are highly expressed by P. aeruginosa in vivo.…”
Section: −10supporting
confidence: 92%
See 2 more Smart Citations
“…We subsequently found that co-culture of pathogens with an anaerobic bacterial consortium composed of taxa commonly found in the lower airways [3,5,27,28] can facilitate robust pathogen growth using mucins as a sole carbon source. We also confirmed that fermentation-derived metabolites are abundant within expectorated CF patient sputum, consistent with previous studies [14,29]. Finally, we found that genes required for the catabolism of mucin fermentation byproducts are highly expressed by P. aeruginosa in vivo.…”
Section: −10supporting
confidence: 92%
“…Moreover, we revealed that in vitro mucin fermentation generated high concentrations of SCFAs and amino acids, which were also abundant and bioavailable for P. aeruginosa within patient sputum. Together, these results suggest that the high levels of utilizable metabolites present in sputum reported previously [14,15,29] may be derived from bacterial mucin degradation. In this context, fermentative anaerobes aspirated from the oral cavity that become established in the lower airways may play a central role in the progression of CF lung disease.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Selected examples include: (1) the short-chain fatty acid receptor GPR41, which is present at higher-than-normal levels in bronchial epithelium of cystic fibrosis (CF) patients and is responsible for exaggerated IL-8 induction in these cells in response to short-chain fatty acids from anaerobic bacteria present in CF lungs [29], (2) the fractalkine receptor CX3CR1, which was recently reported to mediate respiratory syncytial virus-induced cytokine production in primary human airway epithelial cells [30], and (3) an isoform of the coxsackievirus and adenovirus receptor CAREx8a, expressed on the apical surface of airway epithelial cells in culture, that enhances adenovirus entry into cells by coopting neutrophils [31]. …”
Section: Airway Epithelial Cells As the First Line Of Innate Immune Smentioning
confidence: 99%
“…Son et al (44) demonstrated that genes required for the glyoxylate cycle in P. aeruginosa are highly expressed within sputum derived from CF patients, while others have reported that aceA is more highly expressed in CF P. aeruginosa isolates compared to those derived from non-CF sources when isolates are grown in vitro (45). Notably, acetate has also been found at elevated concentrations within CF sputum and bronchoalveolar lavage fluid (34,46,47). Our data, when considered in the context of the aforementioned studies, support a role for the glyoxylate shunt in respiratory mucin degradation by P. aeruginosa.…”
Section: Discussionmentioning
confidence: 99%